Technological innovations at the onset of the Mid-Pleistocene Climate Transition in high-latitude East Asia. Issue 1 (29th March 2020) - Yang, Shi-Xia; Wang, Fa-Gang; Xie, Fei; Yue, Jian-Ping; Deng, Cheng-Long; Zhu, Ri-Xiang; Petraglia, Michael D
Abstract: The interplay between Pleistocene climatic variability and hominin adaptations to diverse terrestrial ecosystems is a key topic in human evolutionary studies. Early and Middle Pleistocene environmental change and its relation to hominin behavioural responses has been a subject of great interest in Africa and Europe, though little information is available for other key regions of the Old World, particularly from Eastern Asia. Here we examine key Early Pleistocene sites of the Nihewan Basin, in high-latitude northern China, dating between ∼1.4 and 1.0 million years ago (Ma). We compare stone-tool assemblages from three Early Pleistocene sites in the Nihewan Basin, including detailed assessment of stone-tool refitting sequences at the ∼1.1-Ma-old site of Cenjiawan. Increased toolmaking skills and technological innovations are evident in the Nihewan Basin at the onset of the Mid-Pleistocene Climate Transition (MPT). Examination of the lithic technology of the Nihewan sites, together with an assessment of other key Palaeolithic sites of China, indicates that toolkits show increasing diversity at the outset of the MPT and in its aftermath. The overall evidence indicates the adaptive flexibility of early hominins to ecosystem changes since the MPT, though regional abandonments are also apparent in high latitudes, likely owing to cold and oscillating environmental conditions. The view presented here sharply contrasts with traditional arguments that stone-tool technologies of China are homogeneous and continuous over the course of the Early Pleistocene.